FASHION, MEDIA AND OLD AGE: considerations based on the documentary Advanced Style (ModaPalavra e-periódico, 2019)
The article discusses the relations between fashion, media and old age, based on an analysis of the documentary Advanced Style. It identifies the representations of the lifestyle that a group of elderly women, with an interest in fashion, establish with aging, consumption and their own body. The themes in the documentary are associated with the cultural context of a society marked by the search for pleasure and happiness, but also by uncertainties and fears. Malaise in Civilization (Freud) and its echoes inPost-Modernity is a central notion in the text and is used to explain the fear of death in the face of the finitude of life. Other notions concerning old age adopted in the text collaborate to explain and put in evidence the existence of new interpretations of old age that have been developing in contemporary society. Relations between consumption, media, fashion and lifestyle are part of the aspects highlighted in the text.
Keywords: old age; fashion and style; consumer culture